Ogoh-Ogoh Kampung Bali Bekasi as a Symbol of Tolerance in Digital Communication and Tradition Preservation - Yudhistira Ardi Poetra (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2025)
The ogoh-ogoh tradition, which is closely associated with the Nyepi celebration, serves not only as a religious ritual but also as a symbol of tolerance and cultural interaction, particularly in Kampung Bali Bekasi. Although the majority of the residents in this area are not of Balinese descent, they actively participate in the ogoh-ogoh celebration, reflecting a process of acculturation and cultural openness. However, despite media coverage, the dissemination of information about this tradition remains limited and has yet to effectively reach a wider audience, especially the younger generation in the digital era. This study aims to analyze how the ogoh-ogoh tradition in Kampung Bali Bekasi serves as a symbol of tolerance and how digital communication contributes to its preservation. The research employs an ethnophenomenological approach, combining ethnographic communication studies and phenomenology. Data collection is conducted through participatory observation and in-depth interviews with community leaders and individuals involved in the ogoh-ogoh celebration. Documentation in the form of the film Bhuta Kala in Tolerance is also used as research data. The findings reveal that digital communication plays a crucial role in introducing and preserving the ogoh-ogoh tradition. Through platforms such as social media, communities can share cultural experiences and foster a broader cross-cultural understanding. Thus, this tradition not only serves as an educational medium but also strengthens social harmony in a multicultural environment.